2018
DOI: 10.1111/iju.13776
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib in combination with everolimus in patients with advanced or metastatic renal cell carcinoma: A phase 1 study

Abstract: Lenvatinib 18 mg and everolimus 5 mg once daily are well tolerated and manageable, and their combined administration has no significant effect on either drug's pharmacokinetics. Overall, this combination therapy shows encouraging antitumor activity in Japanese patients with renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…TRAEs in this study were consistent with the typical class effects of VEGFR and mTOR inhibitors without new safety signals. The grade 3/4 AEs for sunitinib included increased lipase (13%), lymphopenia (12%), neutropenia (11%), hypertension (8%), fatigue (7%), diarrhea (5%), hand-foot syndrome (5%), vomiting (4%) [54], renal AEs were not common in everolimus plus sunitinib [26]. With similar structural features of sunitinib, renal toxicity was also not frequently seen in our study with the exception of proteinuria.…”
Section: Discussionsupporting
confidence: 49%
“…TRAEs in this study were consistent with the typical class effects of VEGFR and mTOR inhibitors without new safety signals. The grade 3/4 AEs for sunitinib included increased lipase (13%), lymphopenia (12%), neutropenia (11%), hypertension (8%), fatigue (7%), diarrhea (5%), hand-foot syndrome (5%), vomiting (4%) [54], renal AEs were not common in everolimus plus sunitinib [26]. With similar structural features of sunitinib, renal toxicity was also not frequently seen in our study with the exception of proteinuria.…”
Section: Discussionsupporting
confidence: 49%
“…Everolimus has also been tested in cervical cancer cell lines with a remarkable ability to inactivate efficiently the HPV16 E7 oncoprotein inhibiting cell proliferation (202). The capacity of everolimus-based combinations to inhibit cell proliferation from several cancer types has been reported for breast cancer (203,204), renal cell carcinoma (205,206), and thyroid cancer (207) in clinical trials.…”
Section: Mtorc1 As a Therapeutic Targetmentioning
confidence: 99%
“…The introduction of tyrosine kinase inhibitors and immunotherapies has remarkably improved the survival of mRCC patients. [1][2][3][4][5][6][7][8][9][10][11][12] Randomized studies suggested the efficacy of first-line nivolumab plus ipilimumab in patients belonging to the intermediate-and poor-risk groups of the IMDC. [13][14][15] However, the efficacy and safety of the first-line nivolumab plus ipilimumab for mRCC patients need to be validated in actual practice, 14 and CheckMate 214 trial only enrolled a limited number of Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of tyrosine kinase inhibitors and immunotherapies has remarkably improved the survival of mRCC patients 1–12 . Randomized studies suggested the efficacy of first‐line nivolumab plus ipilimumab in patients belonging to the intermediate‐ and poor‐risk groups of the IMDC 13–15 .…”
Section: Introductionmentioning
confidence: 99%